Matão Controlling Hypertension (MatCH) project: Rationale and design - Cesar Minelli; Norberto Cabral; Ariany de Souza Leite; Paulo Cicogna Neto; Maria Silvia Vichi; João Luiz Carmo; Fumiu Iwachima; Antônio Durval Martins Peres; Arthur Augusto Ribeiro Ferreira; Flavio Borsetti Neto; Liliana Tiene Ujikawa; Lucileni Aparecida Borin; et al. (Contemporary Clinical Trials Communications, 2017)
Background: Hypertension is the main risk factor for most cardiovascular diseases. A coordinated and organized system from the Brazilian Ministry of Healthy involving Family Health Strategy (FHS), a program for the prevention of chronic disease, and the Popular Pharmacy Program (PPP), which subsidizes medications for the population, could allow an earlier identification and better blood pressure (BP) control. Matão Controlling Hypertension (MatCH) is a community-based population project that aims to apply an organized, integrated and coordinated program in the city of Matão, Brazil, involving FHS and PPP in order to actively search, treat and follow-up hypertensive subjects. Method: This is a population community-based, interventional, follow-up study where all subjects aged ≥ 40 years assisted by the FHS program in Matão will have BP assessed monthly by trained Community Health Agents (CHA) during a domiciliary visit. Identified hypertensive subjects will be referred to FHS physicians for nonpharmacological and pharmacological treatment. Most of the hypertensive drugs used will be available through the PPP. Prevalence of hypertension, awareness, demographics and risk factors will be correlated with BP control. The population study is expected to involve approximately 18.600 subjects. The study period will be four years. Discussion: Considering that hypertension is asymptomatic in most cases, to reduce the population burden of BP-related deaths and diseases it is essential to detect and treat early all hypertensive patients. If we achieve our large-scale BP control, this program can be applied to other populations from developing countries.